PROMOSI KESEHATAN MELALUI APLIKASI TIKTOK TERHADAP PERILAKU PENCEGAHAN KARIES GIGI - Octaviani, Dita; Dewi, Oktavia; Rany, Novita; Marlina, Hastuti; Herniwanti, Herniwanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Dental caries is a non-communicable disease that is often experienced or occurs in children. Damage to the teeth can affect the health of other limbs, so it will interfere with daily activities. Based on Profile Data from the Gajah Mada Community Health Center, Indragiri Hilir Regency (2022), it shows that the second highest proportion of dental caries sufferers are in State Junior High School 2 as many as 46 cases. The purpose of the study was to determine the characteristics of student respondents not caries, and the effectiveness before and after health promotion through the tiktok application on knowledge and attitudes in the prevention of dental caries in State Junior High School 2 Tembilahan. The type of research used is quantitative using a quasy experiment design using a non-equivalent control group design (pretest-postest with control). The research location is at State Junior High School 2 Tembilahan, Indragiri Hilir Regency. The research time is August 2023. The research sample was divided into 2 groups, namely group I (experiment) with counseling with tiktok media as many as 30 students not caries and group II (control) using powerpoint slides (PPT) as many as 30 students not caries. Data analysis was conducted univariately, bivariately, and multivariately. The results of the study of the large characteristics of respondents with male sex were as many as 43 (71.7%) respondents. Knowledge and attitudes have proven effective towards health promotion through tiktok on the prevention of dental caries, with results before and after intervention through tiktok media with a pvalue of 0.000 (pvalue < 0.05). It is hoped that the School can establish advocacy with the Education Office to be able to use tiktok media as one of the educational methods to provide information about dental caries and the prevention of dental caries that is good and correct to students.Keywords : Dental Caries, Knowledge, Health PromotionAttitude, and Tiktok